Financial Freedom, Social Capital, and the Development of Rural Women Entrepreneurship in India - M. Victor; N. Elangovan; D. Halaswamy; M. Sonia (Финансы: теория и практика)
Human resource development can only be achieved by promoting female entrepreneurship. There is a very low level of female entrepreneurship in India, especially in rural areas, which has recently been a cause for concern. Women are now aware of their existence, privileges, and employment circumstances.The subject of this research is female entrepreneurs in rural India, their contribution towards society, problems faced by women entrepreneurs in India, and initial steps taken by the administration for their development in India’s rural region. The research is explanatory. The primary data is used in the paper. The self-structured questionnaire was circulated to the women entrepreneurs in rural India. The data collected was analysed using a targeted sampling method in the Statistical Package for Social Sciences programme, followed by a study of the statistical results. During the survey, 44 respondents were interviewed. The results showed that among the most significant challenges were women’s family responsibilities, gender inequality, financial difficulties, low risk inclination and competition between men and women. It was concluded that the challenges faced by women entrepreneurs could be addressed through appropriate incentives, training, encouragement, social recognition of their entrepreneurial capabilities and appropriate family support.